A global synthesis of the small-island effect in habitat islands. Issue 1889 (24th October 2018) - Wang, Yanping; Chen, Chuanwu; Millien, Virginie
Abstract : Habitat loss and fragmentation are considered to be the leading drivers of biodiversity loss. The small-island effect (SIE) can be used to predict species extinctions resulting from habitat loss and has important implications for species conservation. However, to date, no study has explicitly evaluated the prevalence of SIEs in habitat islands. Here, we compiled 90 global datasets to systematically investigate the prevalence and underlying factors determining the ubiquity of SIEs in habitat island systems. Among the 90 datasets, SIEs were unambiguously detected in 36 cases. We found significant effects of habitat island types and taxon groups on the threshold area of SIEs. The number of islands, area range, species range, island type and taxon group were key variables that determined the prevalence of SIEs. Our study demonstrates that SIEs occur in 40% of cases and thus are common in habitat islands. We conclude that conservation biologists and applied ecologists should consider the prevalence of SIEs when making management strategies in fragmented landscapes.